A quasi-experimental study of a pilot intervention programme among UiTM dental students to curb work-related musculoskeletal disorder as an effect of performing dental extractions / Nursyafinas, Khairil Anuar Md Isa and Tengku Intan - Nursyafinas, Nursyafinas; Md Isa, Khairil Anuar; Tengku Jamaluddin, Tengku Intan Baizura (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
The effects of educational programme and the risk for work-related musculoskeletal disorders (WMSDs) among dental students were investigated. Sixty clinical dental students from year three (first clinical year) and year four (second clinical year) were participated. All participant`s posture while performing dental extractions were analysed by Rapid Entire Body Assessment (REBA) to assess risk of for getting WMSDs. Participants were divided into control group and intervention group respectively from both cohorts. The Extended Nordic Musculoskeletal Questionnaire (NMQ-E) was distributed to assess the presence of pain during last 12-month, last month and today. All received a face to face (F2F) exercise session, exercise note and workout diary. The intervention group received additional educating tool of the exercise video. Post NMQ-E assessment was carried out after 4 weeks. There is statistically significant differences between year three and year four (p<0.00) in which year three had a higher risk to get WMSDs based on REBA. There is no statistically significant differences between pre and post assessment of educational training on each of the body regions based on NMQ-E, neck (p< 0.388), shoulder (p<0.508), upper back (p<0.146), lower back (p<0.118). It can conclude that year three has a higher risk for WMSDs compared to year four. It is imperative that this educational training should be carried out in the dental curriculum along with ergonomic training while performing clinical tasks to curb WMSDs.